2018
DOI: 10.1364/oe.26.011393
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal crystal order and structure revealed by tabletop extreme ultraviolet scattering and coherent diffractive imaging

Abstract: Colloidal crystals with specific electronic, optical, magnetic, vibrational properties, can be rationally designed by controlling fundamental parameters such as chemical composition, scale, periodicity and lattice symmetry. In particular, silica nanospheres -which assemble to form colloidal crystals- are ideal for this purpose, because of the ability to infiltrate their templates with semiconductors or metals. However characterization of these crystals is often limited to techniques such as grazing incidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…X-ray cross-correlation analysis (XCCA), also known as fluctuation X-ray scattering, has been shown to overcome this limitation. Recently, the potential of XCCA has been demonstrated by various theoretical and simulation studies on 2D systems (Altarelli et al, 2010;Kurta et al, 2012;Lehmkü hler et al, 2014;Malmerberg et al, 2015;Latychevskaia et al, 2015;Martin, 2017;Lhermitte et al, 2017) and shown experimentally for thin polymer systems and NPs (Gutt et al, 2014;Schroer et al, 2015;Liu et al, 2017;, liquid crystals (Zaluzhnyy, Kurta, Sulyanova et al, 2017), and colloids and nanocrystals (Mendez et al, 2014;Mancini et al, 2016;Schroer, Westermeier et al, 2016;Mendez et al, 2016;Zaluzhnyy, Kurta, André et al, 2017;Mancini et al, 2018). We previously measured the local orientational order of self-assembled NP films of thicknesses of up to a few micrometres by means of XCCA (Schroer et al, 2015;Lehmkü hler et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…X-ray cross-correlation analysis (XCCA), also known as fluctuation X-ray scattering, has been shown to overcome this limitation. Recently, the potential of XCCA has been demonstrated by various theoretical and simulation studies on 2D systems (Altarelli et al, 2010;Kurta et al, 2012;Lehmkü hler et al, 2014;Malmerberg et al, 2015;Latychevskaia et al, 2015;Martin, 2017;Lhermitte et al, 2017) and shown experimentally for thin polymer systems and NPs (Gutt et al, 2014;Schroer et al, 2015;Liu et al, 2017;, liquid crystals (Zaluzhnyy, Kurta, Sulyanova et al, 2017), and colloids and nanocrystals (Mendez et al, 2014;Mancini et al, 2016;Schroer, Westermeier et al, 2016;Mendez et al, 2016;Zaluzhnyy, Kurta, André et al, 2017;Mancini et al, 2018). We previously measured the local orientational order of self-assembled NP films of thicknesses of up to a few micrometres by means of XCCA (Schroer et al, 2015;Lehmkü hler et al, 2018).…”
Section: Introductionmentioning
confidence: 98%